Symphony for the devil - Steele, Peter; Abruscato, Sal; Silver, Josh; Kelly, Johnny (SPV GMBH, 2006)
Symphony For The Devil is the first Live DVD of the legendary Type O Negative, featuring Pete Steele. The Live DVD features a concert filmed at the Bizarre Festival in Germany 1999, with an awe-inspiring 5.1 sound mix. Bonus features include an audio CD.